Multiagent system technologies : 14th German Conference, MATES 2016, Klagenfurt, Österreich, September 27-30, 2016. Proceedings /: 14th German Conference, MATES 2016, Klagenfurt, Österreich, September 27-30, 2016. Proceedings. (2016) - Unknown
No abstract available